Progress of agriculture in kansas - Odle, James Francis (My University, 1894)
Introduction: When the first settlers began to locate in Kansas many people were anxious to know what the future held in store for the new territory and for the worthy powers who choose to make their homes on Kansas soil. Some of the settlers predicted a flourishing agricultural country immediately, and a rapid accumulation of wealth with but little effort. Others firmly asserted that it was impossible for agriculture to prosper in Kansas, and the people who attempted to till her soil would meet with defeat and disaster. These two reports spread rapidly throughout the eastern and older settled parts of the country. The former report brought into the territory many immigrants who had barely enough means to defray the necessary expense of moving, and possibly enough to support them until they worked to raise a crop. The latter report kept many men of wealth from locating here, or even investing in Kansas enterprises. The agriculture of Kansas began under about as trying circumstances as one can imagine. Many of the early settlers were poor, and what was still worse, they held greatly exaggerated views of the productiveness of Kansas soil. Many of them, it appears, thought that if they could only succeed in locating on a Kansas homestead, the battle was practically won. They would never have attempted to farm under similar circumstances in the older states, even when surrounded by friends and relatives who were able and willing to aid them.
Citation: Odle, James Francis. Progress of agriculture in kansas. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Agriculture; Farming; Crops; Kansas; Theses; Manuscripts (documents)